Chemical composition of manganese nodule samples from the North Pacific Ocean - Bischoff, James L; Piper, David Z; Leong, Kam (Supplement to: Bischoff, JL et al. (1981): The aluminosilicate fraction of North Pacific manganese nodules. Geochimica et Cosmochimica Acta, 45(11), 2047-2063, https://doi.org/10.1016/0016-7037(81)90059-4, 1981)
Nine nodules collected from throughout the deep North Pacific were analyzed for their mineralogy and major-element composition before and after leaching with Chester-Hughes solution. Data indicate that the mineral phillipsite accounts for the major part (> 75%) of the aluminosilicate fraction of all nodules. It is suggested that formation of phillipsite takes place on growing nodule surfaces coupled with the oxidation of absorbed manganous ion. All the nodules could be described as ternary mixtures of amorphous iron fraction (Fe-Ti-P), manganese oxide fraction (Mn-Mg Cu-Ni), and phillipsite fraction (Al-Si-K-Na), these fractions accounting for 96% of the variability of the chemical composition.